Left ventricular thrombus as a rare complication of pulmonary tuberculosis - Amit Kumar; Aman Dubey; Yogesh Sanwaria; Shweta Tanwar (Exploration of Cardiology, 2025)
Tuberculosis (TB) continues to pose a significant public health burden in endemic regions, remaining a leading cause of morbidity and mortality. Although TB is associated with a range of complications, the occurrence of intracardiac thrombus is an exceptionally rare manifestation. We report the case of a 62-year-old male with active pulmonary TB, who had been on anti-tubercular therapy for one month and presented with recurrent syncope and exertional dyspnea. Transthoracic 2D echocardiography revealed a large, mobile thrombus in the left ventricular apex. Evaluation for underlying hypercoagulable states was unremarkable. The patient was managed with anticoagulation therapy in conjunction with ongoing anti-tubercular treatment. This case underscores the importance of clinical vigilance for rare thrombotic complications in TB to facilitate timely diagnosis and appropriate management.